2009
DOI: 10.1177/0261927x09341954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Speech of Younger and Older Adults: Age, Gender, and Speech Situation

Abstract: This study examines how listeners arrive at judgments of speech as irrelevant or off-topic (off-target). Older adults and college students evaluated a set of narratives ascribed to speakers differing in age and gender and presented as conversations or interviews. The results show that young and old adults bring different understandings of age and situation to the evaluation task. Older evaluators judged narratives more on-target than younger evaluators. Differences between evaluator age groups were also observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Varying the age of the listener allowed me to tap into the differences in speech modifications based on with whom the participant was engaging in a task. The fictive listener technique was used successfully with older adults in previous research (Odato & Keller-Cohen, 2009). In that study, older and younger adults were shown pictures of fictive listeners differing by gender and age and were asked to make judgments about narratives attributed to the fictive listener.…”
Section: Methodsmentioning
confidence: 99%
“…Varying the age of the listener allowed me to tap into the differences in speech modifications based on with whom the participant was engaging in a task. The fictive listener technique was used successfully with older adults in previous research (Odato & Keller-Cohen, 2009). In that study, older and younger adults were shown pictures of fictive listeners differing by gender and age and were asked to make judgments about narratives attributed to the fictive listener.…”
Section: Methodsmentioning
confidence: 99%
“…This would suggest that first-year students may have inflated their ratings of the higher quality language skills of older adults compared to younger adults. Odato and Keller-Cohen (2009) also found that younger adults rated older adult speakers more positively. This could suggest that first-year students have a negative stereotype of the older adult, causing them to expect poor language skills.…”
Section: Evidence Of Stereotypesmentioning
confidence: 76%
“…Therefore, we can hypothesize that the relevance of conversation may decline with age. Yet, increased off-topic verbosity does not appear to be negatively stereotyped, as demonstrated by Odato and Keller-Cohen (2009). This would suggest that, even if relevance declines with age, interlocutors might not perceive relevance as a primary factor when judging older adults' communication.…”
Section: Relevancementioning
confidence: 86%
See 2 more Smart Citations